Resveratrol prevents gallstones in mice fed on a high fat diet via regulating PPAR-γ and SR-BI - Zhao, Menglu; Xie, Boya; Li, Yuxuan; Dong, Haiqing; Jiang, Sijia; Zhu, Tiantian; Wu, Xiaolong; Xu, Chengchen; Zhang, Jian; Sun, Shiyi; Li, Rui; Xie, Yinghai (Frontiers in Pharmacology, 2025)
BackgroundWith the gradual improvement of living standards, the incidence of gallstones is getting higher and higher, and cholesterol gallstones (CG) are the most prevalent subtype. Therefore, we urgently need a better way to treat gallstones.ObjectiveThis study aimed to evaluate the effects of resveratrol (Res) on cholesterol gallstone formation and explore its underlying mechanisms, focusing on its modulation of hepatic peroxisome proliferator-activated receptor γ (PPAR-γ) expression, bile cholesterol saturation, and hepatic cholesterol metabolism.MethodsThirty-two male C57BL/6 mice were randomly divided into four groups: control, model, ursodeoxycholic acid (UDCA), and Res groups. Res (100 mg/kg/day) and UDCA (100 mg/kg/day) were administered via gavage for 5 weeks. Gallbladder bile, liver, and gallbladder tissues were collected for bile cholesterol crystal analysis, bile lipid profiling, and histopathological examination. Protein expression levels of PPARγ and scavenger receptor class B type I (SR-BI) were analyzed using Western blotting and immunohistochemistry.ResultsMice fed on a high fat diet resulted in larger gallbladder (about 2 times in both long and width diameters compared to control group) and CG formation, while resveratrol treatment significantly reduced gallstone formation, improved gallbladder dilatation, and declined cholestasis symptoms. Res suppressed hepatic inflammation by downregulating the receptor for advanced glycation end products (RAGE) expression and inhibiting the synthesis of proinflammatory factors. Res alleviated liver lipid deposition. It also enhanced PPARγ and SR-BI expression, promoting cholesterol efflux and lowering cholesterol levels, thereby preventing CG formation in mice.ConclusionResveratrol demonstrates significant potential as a therapeutic agent for the prevention and treatment of cholesterol gallstone disease (CGD) by modulating hepatic cholesterol metabolism, reducing bile cholesterol saturation, and alleviating hepatic inflammation. Further studies are warranted to explore its clinical applicability in humans.